2018
DOI: 10.1177/1533033818799355
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Radiotherapy With SBRT or IMRT Boost for Breast Cancer: Excellent Local Control and Cosmetic Outcome

Abstract: The gold standard for breast cancer treatment is surgery, but many women may desire to avoid surgery if possible. The purpose of this study was to evaluate whether breast cancer could be cured with modern sophisticated radiation techniques with good cosmetic outcome. We have treated 18 patients with operable breast cancer by conventional whole-breast irradiation followed by stereotactic body radiotherapy (primary tumor only) or intensity-modulated radiotherapy (tumor plus axillary nodes) boost. The planned dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Regarding radical SBRT, there are even fewer reports. Shibamoto et al reported that they performed whole breast irradiation and SBRT boost with the radiosensitizer KORTUC [ 20 ] for 18 patients who refused surgery, and only one case developed local recurrence [ 21 ]. Barry et al [ 22 ] reviewed SBRT for breasts and reported that five neoadjuvant setting phase I/II trials were underway, including the ARTEMIS trial in Canada and the ABLATIVE trial in the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding radical SBRT, there are even fewer reports. Shibamoto et al reported that they performed whole breast irradiation and SBRT boost with the radiosensitizer KORTUC [ 20 ] for 18 patients who refused surgery, and only one case developed local recurrence [ 21 ]. Barry et al [ 22 ] reviewed SBRT for breasts and reported that five neoadjuvant setting phase I/II trials were underway, including the ARTEMIS trial in Canada and the ABLATIVE trial in the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding radical SBRT, there are even fewer reports. Shibamoto et al reported that they performed whole breast irradiation and SBRT boost with the radiosensitizer KORTUC 20 for 18 patients who refused surgery, and only one case developed local recurrence 21 . Barry et al reviewed SBRT for breasts and reported that ve neoadjuvant setting phase I / II trials were underway, including the ARTEMIS trial in Canada and the ABLATIVE trial in the Netherlands 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, for example, it is now the standard treatment option for early-stage inoperable non-small cell lung cancer due to its superior e cacy. [9] Likewise, SBRT plays an important role in hepatopulmonary metastases from colon and breast cancers [10][11] . For patients with recurrence and metastasis, several small, single-institution retrospective studies have shown that SBRT has a relatively high local control rate and low toxicity in the treatment of sarcoma PM [19][20][21] .…”
Section: Discussionmentioning
confidence: 99%